Enhancing public understanding of extreme weather events in a changing climate through ClimaMeter - Faranda, Davide (Frontiers in Climate, 2025)
ClimaMeter is a real-time platform designed to provide rapid, science-based assessments of extreme weather events and their links to climate change. ClimaMeter’s methodology relies on identifying large-scale atmospheric circulation patterns and comparing them to historical data, analyzing how the intensity of extreme weather events have changed because of anthropogenic climate change or natural climate variability. By leveraging historical climate data, machine learning, and real-time weather observations, ClimaMeter delivers near-instantaneous attribution results, enabling informed decision-making in a time when media cycles and public attention are brief. This speed is crucial for climate action, as it helps policymakers, emergency responders, and the public understand the role of climate change in specific extreme events and take timely, effective measures. This allows for quicker, data-driven responses to disasters, such as the October 2024 Valencia floods or the Medicane Daniel, by informing disaster response, infrastructure planning, and resilience-building efforts. ClimaMeter also plays a key role in countering climate change misinformation, offering evidence-based explanations to the public and media. By bridging the gap between scientific research and policy applications, ClimaMeter supports climate action, promotes public awareness, and aids in the development of adaptation and mitigation strategies to address the growing risks posed by climate change.